(untitled) (Research, Society and Development, 2021)
This study evaluated the effect of disinfection procedures and exposure to 0.9% NaCl solution cycles during sterilization, on the electrochemical, physical and chemical properties of different stainless steel alloys used in the biomedical field. Discs of F899 XM16, F899 303, and F899 420B alloys were cleaned with enzymatic detergent followed by 20 cycles of autoclave sterilization. Electrochemical tests were performed including open circuit potential, electrochemical impedance spectroscopy, and potentiodynamic polarization tests in 0.9% NaCl (n=5). Surface characterization was performed using scanning electron microscopy (SEM), energy dispersive spectroscopy, and surface roughness and microhardness both before and after the electrochemical test. Quantitative data were analyzed with a significance level of 5%. The corrosion current density and corrosion potential of the alloys did not present statistical differences. The capacitance values of the three oxide layers, polarization resistance, and impedance of Warburg were similar among the alloys. Considering the topography, surface roughness increased for all alloys in the post-corrosion period. The stainless steel alloys analyzed were negatively affected at the electrochemical behavior, corrosion kinetics, and surface characterization after the 0.9% NaCl solution and the autoclave sterilization cycles, confirming the need for regular exchanges of surgical instruments and drills used in medical and dental implantology.